Effects of Different Nitrogen Fertilizers and Humic Acid On Wheat Crop Irrigated With Different Water Regime Using 15N (Bangladesh Journal of Botany, 2021)
A field experiment was conducted to observe effects of water requirements and different fertilizers on wheat crop’s yield, production and N uptake. Data showed that dry matter yield of wheat grain was higher with Hu + AS (5.82 mt/ha) compared with applied water 100% ETC. Concerning the rate of water regime, the best significant grain yield of wheat was obtained with 100% ETc (4.23 mt/ha). Nitrogen derived from fertilizer Ndff% with 50% ETC of water was 28.41 and 27.28% for grain and straw, respectively. At 100% ETC of water the Ndff% was 30.16 and 27.75% for grain and straw, respectively. Nitrogen utilized by grains and straw was more efficient under treatment Hu + AS combined with 50% Etc, 100% Etc recording 15.6 and 32.23%, respectively. At 50% ETC of water requirements for wheat crop, higher N remained in 0 - 15, 15 - 30 and 30 - 45 cm soil depth were nearly closed to each other compared with the treatment made at 100% ETC of water requirements.Bangladesh J. Bot. 50(2): 261-267, 2021 (June)